2014
DOI: 10.3122/jabfm.2014.03.130152
|View full text |Cite
|
Sign up to set email alerts
|

Provider Perspectives on Integrating Primary and Behavioral Health: A Report from the High Plains Research Network

Abstract: Background: Integrated primary care, a health care delivery model that combines medical and behavioral health services, provides better patient access to care at a lower cost, with better outcomes compared with usual nonintegrated care models. The perspectives of primary care providers (PCPs) and behavioral health care providers (BHPs) toward integration are especially valuable because their input and endorsement are key to successful and sustained integration. However, there is little research assessing or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Assessments of referral practices and methods included referral method preferences (e.g., by email or pager; Burfeind, Seymour, Sillau, Zittleman, & Westfall, 2014; Pratt et al, 2012) and preferred referral methods when BHCs were occupied with other patients at time of need (Davis et al, 2013). The evaluations of referral practices and methods (see code “REF-P” in Table 6) provided evidence that face-to-face referrals (e.g., warm handoffs) were preferred by BHCs and PCPs, and were typically more successful than alternate referral methods (e.g., flags in the medical record).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessments of referral practices and methods included referral method preferences (e.g., by email or pager; Burfeind, Seymour, Sillau, Zittleman, & Westfall, 2014; Pratt et al, 2012) and preferred referral methods when BHCs were occupied with other patients at time of need (Davis et al, 2013). The evaluations of referral practices and methods (see code “REF-P” in Table 6) provided evidence that face-to-face referrals (e.g., warm handoffs) were preferred by BHCs and PCPs, and were typically more successful than alternate referral methods (e.g., flags in the medical record).…”
Section: Resultsmentioning
confidence: 99%
“…Reimbursement. In these studies, researchers assessed the payment methods, policies, and practices related to reimbursement for IBHC services (Burfeind et al, 2014;Ellison, 2014;Kessler et al, 2014; see code "REIMB" in Table 6).…”
Section: The Financial Worldmentioning
confidence: 99%
“…Barriers to transferring patient care can be categorized into three broad categories: care coordination, provider/patient capability and beliefs, and support structures. Care-coordination barriers highlight that an intervention to increase care transitions can involve a role change for PC providers and may require attention to communication processes and workload challenges (e.g., Benzer et al, 2015; Burfeind, Seymour, Sillau, Zittleman, & Westfall, 2014). Barriers around capabilities and beliefs suggest that transitions can sometimes be threatening to patients and providers (e.g., Brez et al, 2009; Forrest, Nutting, von Schrader, Rohde, & Starfield, 2006).…”
Section: Barriers To Care Transitions From Specialty Care To Primary ...mentioning
confidence: 99%
“…Given that colocation should help providers interact regarding the care of individual patients, integrated care is likely more difficult in rural areas. Yet Burfeind et al 16 reported differing opinions on integrating mental health and primary care services by the respective providers. 18 report on improvements in asthma care and guideline adherence through a group self-assessment module.…”
Section: Mental and Behavioral Health Care Assessment In (And With) Fmentioning
confidence: 99%